2020
DOI: 10.12691/ajmcr-8-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Anaplastic and Papillary Thyroid Carcinomas: A Case Report

Abstract: Anaplastic thyroid cancer (ATC) is a rare, but extremely aggressive, form of cancer with a high mortality rate. Differentiated thyroid cancer (DTC), on the other hand, including papillary and follicular subtypes, are relatively common and typically follows a more indolent course. Cases have been reported in which ATC transforms from DTC, and where DTC and ATC exist simultaneously. Given the low incidence of such cases, they have not been well studied, and the optimal treatment regimen has yet to be determined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…ATC is the most aggressive form of thyroid malignancy, with studies showing a high mortality rate of 33-50%, a median survival of three to four months, and less than 20% survival of one year [1][2][3][4]. Most patients will present with sudden enlarging of neck mass, and no less than 40% of the patients have distant metastases at the time of diagnosis [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ATC is the most aggressive form of thyroid malignancy, with studies showing a high mortality rate of 33-50%, a median survival of three to four months, and less than 20% survival of one year [1][2][3][4]. Most patients will present with sudden enlarging of neck mass, and no less than 40% of the patients have distant metastases at the time of diagnosis [1].…”
Section: Discussionmentioning
confidence: 99%
“…Differentiated thyroid carcinoma (DTC), on the other hand, including follicular and papillary subtypes, are more common. Papillary thyroid carcinoma (PTC) alone accounts for 85% of all thyroid carcinomas [ 3 ]. Here, we report a case of thyroid carcinoma with concurrent anaplastic and follicular variants of the papillary subtype component presenting as thyrocutaneous fistula with pus discharge.…”
Section: Introductionmentioning
confidence: 99%
“…This combination is approved by the FDA, and a central radiology review demonstrated an overall response rate of 69%[ 21 ]. In one patient, dabrafenib/trametinib therapy was well tolerated, and the patient lived for more than six months[ 22 ]. To date, no medications targeting TERT or telomerase have been developed.…”
Section: Discussionmentioning
confidence: 99%
“…ATC is usually diagnosed after it has already spread and is one of the most incurable cancers. The tumors can be very complex, with 20-30% of ATC patients having tumor areas with ATC and PTC histology [15]. Malignant bone and cartilage formation has also been observed and the descriptive term "carcinosarcoma" as subtype of ATC has been suggested by the WHO but this classification is not uniformly accepted.…”
Section: Thyroid Carcinomamentioning
confidence: 99%